The Effect of Using Poster Media towards Students' Learning Outcomes of Thematic Learning at Grade III SD Negeri 01 Ulak Karang Selatan - Nadia Safitri; Nofriza Efendi; Ayunis Ayunis; Stavinibelia Stavinibelia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This research aims to improve student learning outcomes by using poster media in Thematic learning on Theme 5 Subtheme 3 Lessons 1, 2 and 3 Concerning the Influence of Weather Changes on Human Life. This research is experimental research using poster media carried out in 2 classes. The subjects in this research were class III students at SDN 01 Ulak Karang Selatan, in class A there were 26 students and in class D there were 21 students. Student learning outcomes are also measured from student learning results sheets and LKPD sheets at each meeting. Judging from the results of this research, the use of poster media can improve student learning outcomes in class III Shiva Thematic learning at SD Negeri 01 Ulak Karang Selatan. It can be seen in the difference in the average score of the pretest for the Experimental Class 64.81 and the posttest for the Experimental Class 80.81, while the average result of the pretest for the Control Class is 57.15 and the posttest for the Control Class is 69.54, then it can also be seen in the T test hypothesis The obtained sig is significant. (2-tailed) 0.00 < 0.05, then according to the basis for decision making in the independent T-Test sample test, it can be concluded that Ho is rejected and Ha is accepted.